System of the Regional Executive Power in the USSR at a Boundary of the 1920-1930 th Years - Alexander Yurievich Saran (Управленческое консультирование)
In the article the condition of executive power in the USSR at the regional level at a boundary of the 1920-1930th on the example of Central Black Earth Region is analyzed. Experience of administrative-territorial reforms on creation of mega-areas is investigated in application to the present.